Instrumen Zakat Sebagai Sumber Penerimaan Dan Pengeluaran Keuangan Negara - Onti Laura Citra; Yuyun Yuniara; Idia Jonionda Piolita; Andi Cahyono (Kota Bengkulu, Provinsi Bengkulu, Indonesia, 2023)
Abstract: The purpose of this study is to discuss the essence of zakat as an Islamic financial instrument as a source of state financial revenue and expenditure in the view of Muhammad Nejatullah Siddiqi. Using qualitative methods, which are methods that produce descriptive data in the form of written or spoken words. The results of this study show that Muhammad Nejatullah Siddiqi is one of the contemporary Islamic economics from the mainstream class. The idea of zakat has always been linked to Islamic economics. Zakat is an obligation of the rich, the rights of the poor, and the state has an important role in its management. It contains moral, social, and economic aspects. Zakat is the axis and financial center of the country. Its position on the one hand can be a potential source for alleviating poverty, on the other hand it can be a working capital for the poor in order to open jobs. It can even be used as the last shield for the economy so that it does not slump when consumption ability stagnates. Thus, it can be concluded that zakat instruments can be used as a source of state financial receipts and expenditures. So it can be suggested to increase zakat instruments as a source of state financial revenue in Indonesia.Keywords; Zakat Instruments, Sources of Revenue and Expenditure, State Finance. Abstrak: Tujuan penelitian ini untuk membahas tentang esensi zakat sebagai instrumen finansial Islami sebagai sumber penerimaan dan pengeluaran keuangan Negara dalam pandangan Muhammad Nejatullah Siddiqi. Menggunakan metode kualitatif, yaitu metode yang menghasilkan data yang berupa deskriptif berupa kata-kata tertulis atau lisan. Hasil penelitian ini memperlihatkan bahwa Muhammad Nejatullah Siddiqi merupakan salah satu ekonomi Islam kontemporer dari golongan mainstrem. Pemikiran tentang zakat senantiasa terkait dengan ekonomi Islam. Zakat merupakan kewajiban orang-orang kaya, hak orang-orang miskin, dan negara mempunyai peran penting dalam pengelolaannya. Di dalamnya mengandung aspek moral, sosial, dan ekonomi. Zakat adalah poros dan pusat keuangan negara. Kedudukannya satu sisi dapat menjadi sumber potensial untuk mengentaskan kemiskinan di sisi lain dapat menjadi modal kerja bagi orang miskin agar dapat membuka lapangan pekerjaan. Bahkan dapat dipergunakan sebagai perisai terakhir bagi perekonomian agar tidak terpuruk ketika kemampuan konsumsi mengalami stagnasi. Dengan demikian dapat disimpulkan bahwa instrument zakat dapat dijadikan sebagai sumber penerimaan dan pengeluaran keuangan Negara. Sehingga dapat disarankan tingkatkan instrument zakat sebagai sumber penerimaan keuangan Negara di Indonesia.Kata Kunci; Instrumen Zakat, Sumber Penerimaan dan pengeluaran, Keuangan Negara